2001
DOI: 10.3310/hta5110
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of autologous chondrocyte transplantation for hyaline cartilage defects in knees: a rapid and systematic review

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents, York Publishing Services by:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 72 publications
1
21
0
Order By: Relevance
“…Moreover, iron oxide labeling of chondrocytes may have immediate applicability in current tissue repair therapies such as autologous chondrocyte implantation. [39][40][41][42][43] Heymer et al 44 were the first to report on SPIO labeling specifically for the purposes of cartilage tissue engineering. Their studies showed that bone marrow-derived stem cells could still differentiate chondrogenically while retaining intracellular iron oxide, thereby permitting MRI detection within 3D collagen type I hydrogel constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, iron oxide labeling of chondrocytes may have immediate applicability in current tissue repair therapies such as autologous chondrocyte implantation. [39][40][41][42][43] Heymer et al 44 were the first to report on SPIO labeling specifically for the purposes of cartilage tissue engineering. Their studies showed that bone marrow-derived stem cells could still differentiate chondrogenically while retaining intracellular iron oxide, thereby permitting MRI detection within 3D collagen type I hydrogel constructs.…”
Section: Discussionmentioning
confidence: 99%
“…2 If the injury is initially restricted to the aneural cartilage, an extended period of uninhibited use may separate the inciting incident from the onset of clinical signs. 3,4 Consequently, many affected individuals may be middle-aged or older on first presentation.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Osteochondral autografts are technically demanding, have associated donor site morbidity, and work best in younger patients, 5 and allografts have the added risks of disease transmission and immune-mediated rejection. 8 While greater than 70% of patients undergoing autologous chondrocyte transplantation have had a good or excellent outcome 2 or more years postsurgery, 3 the procedure is lengthy and expensive, it is contraindicated in the presence of existing osteoarthritis, 9,10 and it has a demanding convalescence program.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews "Effectiveness of autologous chondrocyte transplantation for hyaline cartilage defects in knees: a rapid and systematic review" [2].…”
Section: Resultsmentioning
confidence: 99%